A Comparative Study Of Using Cofe Switching And Code Mixing Method On Eleventh Grade Students’ Speaking Ability At SMK Tunas Pelita Binjai - Yultisa, Nudia; Panjaitan, Efrini; Salsabila, Muftia; Rahmah, Maulidya (BEST Journal (Biology Education, Sains and Technology), 2024)
The aim of this research 1) to explore the type of each method that frequently used by the eleventh-grade students of SMK Tunas Pelita Binjai, 2) to identify which method is more often used by the eleventh-grade students of SMK Tunas Pelita Binjai. Data were analysed using descriptive qualitative methods. Data were obtained from speaking tests administered to students in group in front of the class. The types of code-switching, namely Tag-switching, Inter-sentential, and Intra-sentential, were analysed based on Appel and Muysken theory. As a result, students frequently used Intra-sentential type of code-switching at a rate of 72%, Inter-sentential at a rate of 40,4%, and finally used Tag-switching at a rate of 0%. Types of code-mixing, namely Insertion, Alternation and Congruent Lexicalization, were analysed based on Muysken theory. The results showed that 70,2% of the students frequently used the Insertion type of code-mixing, while the rate of the Alternation was 21,2%, and the rate of Congruent Lexicalization was 0%. Above all, the results showed the students used code-switching more frequently during the conversation test with total 112,4%, while the code-mixing showed the total 91,4%.